Arbitration as a forum for dispute resolution and climate change disputes - Fernández Pérez, Ana (CUADERNOS DE DERECHO TRANSNACIONAL, 2022)
Sustainability is the main challenge for humanity. At the current moment in history, the sustainability challenge is a direct consequence of human activity. Addressing challenges, requires action and costs, and the distribution of costs is a querulous, political issue. Climate change-related disputes already occupy numerous state and international courts, can arbitration tribunals play a role in resolving such or similar disputes? This study aims to examine arbitration as a forum for dispute resolution in an environmental and climate change–related case that can play a role in promoting compliance with international climate change law. This question arises from the fact that international climate change law has entered a new phase, while the number of disputes related to the environment and climate change has recently increased. The lack of an enforcement mechanism under the Paris Agreement will lead to new problems. The research result shows that arbitration, as one of the means of dispute resolution, becomes an alternative solution to address this issue. Procedural flexibility, high levels of expertise among arbitrators and the ability to enforce awards in virtually any country in the world under the New York Convention are some of the attributes of arbitration that make it an attractive and effective method for resolving climate change disputes. These qualities allow parties to arbitration to set the rules that best suit the needs of their case, from setting the timing of the parties’ briefs to creating rules for the presentation of evidence, the request for documents and participation in hearings. In addition, the parties also play a key role in the appointment of arbitrators, who are experts in the matters in dispute and whose training and experience enables them to fully understand highly specialised and technically complex arguments and evidence. Arbitration has the function of creating predictability and certainty, so this forum could serve to promote compliance with international climate change law.
Keywords: Climate change; climate justice 2015; Paris Agreement; arbitration; climate change disputes